Methods for recommending and predicting Nobel Prize candidates. Issue 2 (2014) - Guo Gen‐Ming; Chen Hui‐Shan
<x xml:space="preserve"> Abstract </x> Purpose – In the twenty‐first century, technology and information are continuously being changed and rapidly updated. Many new innovations and discoveries emerge daily. This study aims to identify significant pioneers and milestones in academic research through utilizing bibliometric methods and heterogeneous data, including textbook citations, citations of theses and dissertations, and journal citations. Design/methodology/approach – This study proposes several methods and formulas for recommending Nobel prizes candidates. Through utilizing bibliometric methods and heterogeneous data, including textbook citations, citations of theses and dissertations, and journal article citations, this research facilitates the collection of numerous significant research results. The authors propose several new, useful formulae, including a pioneer paper impact factor, a popular classical paper impact factor, a ranking factor of specific fields, a groundbreaking author impact factor, and a frequently cited author impact factor. Findings – This study utilizes historical information on the Nobel Prize to examine, revise, and verify existing methods for recommending and predicting candidates, in order to enhance the accuracy and availability of the approach presented by this study. The experimental results show that the approach designed in this study had a rate of successful prediction exceeding 50 percent. The major reason for producing reasonable results is that the milestone paper and pioneer paper are filtered first, and then the important candidate authors from the most pioneer paper are filtered. Therefore, the results indicated the feasibility of the methods developed by this study. Originality/value – The purpose of the Nobel Prize is to reward original research findings or inventions that significantly and positively influence human life. However, due to budget limitations, only five fields are included in the academic domains for which Nobel prizes are awarded. The authors develop one useful new way to identify milestone papers and authors. Young students can choose, read and learn from these milestone papers. The pioneer authors identified by this research could be the recommended candidate list for some academic awards.